The Cattle Mandibles, Cranial Fragments and Metapodials from the Burgstraat in Ghent (Belgium) - Emmy Nijssen (Papers from the Institute of Archaeology, 2017)
The Burgstraat is an archaeological site which is located within the high-medieval part of the town of Ghent. Excavations conducted by BAAC Vlaanderen in 2011 revealed numerous structures, artefacts and ecofacts at the site - some of which date to the 12th century. This paper focuses on SP141, a 13th century waste deposit. The contents of SP141 are mostly zooarchaeological remains. The investigated sample consists of 2652 animal bone fragments, which predominantly represent domestic cattle (Bos p.f. Taurus). Interestingly, this large concentration of cattle remains consists primarily of cranial fragments. At the Burgstraat, mandibles and maxillae appear to have been divided in a systematic manner of butchery. The function of the processing of the cranial parts presents part of an economic chain where animals are brought into the urban economic system for their meat, horn, hide and bone. This paper explores the role of the cattle remains from SP141, and presents the results of preliminary analyses at the site, including age and demographic data.